Dampak Disiplin Kerja terhadap Kemampuan Kinerja Aparatur Nagari dalam Pengelolaan Keuangan Nagari di Kecamatan Banuhampu dan Sungai Pua - Yanti, Rahmi (JESS (Journal of Education on Social Science); Vol 3 No 1 (2019): Relationship between Government and CommunityDO - 10.24036/jess/vol3-iss1/171, 2019)
The purpose of this study is to analyze the impact of work discipline on the performance capabilities of the nagari apparatus in nagari financial management in Banuhampu and Sungai Pua Districts. The population used in this study were all nagari apparatus in Banuhampu and Sungai Pua Subdistricts of 80 people, while the samples used as many as 75 respondents were determined by the Slovin formula using the proportionate stratified random sampling technique. Data collection in this study was conducted using a questionnaire with a Likert scale measurement and analyzed using multiple linear regression. The results of this study indicate that the work discipline of the nagari apparatus is relatively high while the performance of the nagari apparatus is still low and the results of the regression test explain that work discipline has an impact on the performance capabilities of the nagari apparatus in nagari financial management in Banuhampu and Sungai Pua Districts.